EFEKTIFITAS LEMBAGA PEMASYARAKATAN DI INDONESIA - Yunardhani, Rakei (JURNAL SOSIOLOGI, 2013)
This This paper reviews about the effectiveness of prisons in Indonesia. The limit in this paper include: the purpose of the SPP; indicator of the effectiveness of prisons, and; facts in Indonesian prisons. At the end of this paper, an alternative solution is also presented in order to realize effective in Indonesian prisons.